"The influence of olfactory enrichment on the behavior of two captive New World primates: Black‐capped capuchin (Sapajus apella) and common marmoset (Callithrix jacchus)". Issue 2 (20th September 2022) - Wowk, Zoia M.; Behie, Alison M.
Abstract: Environmental enrichment is an animal husbandry principle that seeks to provide the stimuli necessary for the optimal physiological and psychological well‐being of animals. Due to primates having highly developed visual systems, there have been limited attempts to quantify the benefit of olfactory enrichment on captive primate populations. We aim to investigate how a range of odors may influence the behaviors of two captive New World primate species that have varying reliance on olfactory pathways, black‐capped capuchin ( Sapajus apella ) and common marmoset ( Callithrix jacchus ), at the National Zoo and Aquarium, Canberra, Australia. We presented three odors (rosemary oil, Salvia rosmarinus, banana essence and white‐tailed deer urine, Odocoileus virginianus ) four different times to the two species following a 12‐week randomized schedule. Using instantaneous scan sampling we collected behavioral and direct cloth interaction (DCI) data on 40 days. We then calculated activity budgets. Results show both species significantly respond to different olfactory conditions. S. apella responded to banana by decreasing inactivity ( df = 4, F = 6.600, p = .007), and increasing DCI frequencies ( df = 3, F = 116.196, p < .0001) whereas C. jacchus was influenced by rosemary and deer urine—also reducing inactivity levels ( df = 4, F = 15.938, p < .0001), but not changing DCI frequencies. We also tested habituation however it is not significant for either species over the course of the study. This comparative investigation is one of the first of its kind and uncovers the possibility for olfactory stimulus to be successfully used as a type of beneficial environmental enrichment for captive primates, supporting the constructive and ongoing development of enrichment programs at captive facilities. Abstract : Two New World primate species, Sajapus apella and Callithrix jacchus, significantly behaviorally responded to olfactory enrichment to varying degrees of change (i.e., influence) and odor conditions. This comparative investigation uncovers the possibility for olfactory stimulus to be used as a type of beneficial enrichment for captive primates. Research Highlights: We exposed a range of odors to two captive primate species, S. apella and C. jacchus . Both species significantly behaviorally responded to enrichment to varying degrees. This comparative investigation reveals the benefits of olfactory enrichment.